2010
DOI: 10.5351/ckss.2010.17.6.909
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Predictive Coverage Growth Function

Abstract: A trend in software reliability engineering is to take into account the coverage growth behavior during testing. A coverage growth function that represents the coverage growth behavior is an essential factor in software reliability models. When multiple competitive coverage growth functions are available, there is a need for a criterion to select the best coverage growth functions. This paper proposes a selection criterion based on the prediction error. The conditional coverage growth function is introduced fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This section illustrates application of the virtual coverage metric to CGF. Park and Lee (2010) fitted three CGFs to DS3 and found that the lognormal CGF…”
Section: Application Of Virtual Coverage Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…This section illustrates application of the virtual coverage metric to CGF. Park and Lee (2010) fitted three CGFs to DS3 and found that the lognormal CGF…”
Section: Application Of Virtual Coverage Metricmentioning
confidence: 99%
“…In this context Park et al (2003Park et al ( , 2004 and Fujiwara et al (2007) considered SRGMs in terms of coverage and not testing time. In order to relate such SRGMs to the testing time, Park and Fujiwara (2006), Park et al (2007Park et al ( , 2008a and Park and Lee (2010) studied CGFs. Crespo et al (2008Crespo et al ( , 2009) recently proposed new SRGMs that simultaneously incorporate testing time and coverage.…”
Section: Introductionmentioning
confidence: 99%